Herpes Zoster in Solid Organ Transplantation: Incidence and Risk Factors - Kho, Marcia M. L.; Roest, Stefan; Bovée, Dominique M.; Metselaar, Herold J.; Hoek, Rogier A. S.; van der Eijk, Annemiek A.; Manintveld, Olivier C.; Roodnat, Joke I.; van Besouw, Nicole M. (Frontiers in Immunology, 2021)
Background: Studies on herpes zoster (HZ) incidence in solid organ transplant (SOT) recipients report widely varying numbers. We investigated HZ incidence, severity and risk factors in recipients of 4 different SOT, with a follow-up time of 6-14 years. Methods: Records of 1033 transplant recipients after first heart (HTx: n=211), lung (LuTx: n=121), liver (LiTx: n=258) and kidney (KTx: n=443) transplantation between 2000 and 2014 were analysed for VZV-PCR, clinical signs of HZ and complications. Results: HZ was diagnosed in 108 of 1033 patients (10.5%): 36 HTx, 17 LuTx, 15 LiTx and 40 KTx recipients. Overall HZ incidence rate after HTx (30.7 cases/1000 person-years (PY)), LuTx (38.8 cases/1000 PY), LiTx (22.7 cases/1000 PY) and KTx (14.5 cases/1000 PY) was significantly higher than in the general 50-70 year population. Multivariable analysis demonstrated age ≥50 years at transplantation (p=0.038, RR 1.536), type of organ transplant (p=0.002), CMV prophylaxis (p=0.043, RR 0.631) and type of anti-rejection therapy (p=0.020) as significant risk factors. Complications occurred in 33 of 108 patients (14/36 HTx, 8/17 LuTx, 3/15 LiTx, 8/40 KTx): post-herpetic neuralgia, disseminated disease and cranial nerve involvement. Conclusion: HZ incidence and severity in SOT recipients is most pronounced after heart and lung transplantation, in older patients and when CMV prophylaxis is lacking.